2016
DOI: 10.1530/eje-16-0177
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and metabolic diurnal rhythms in young adult men born small vs appropriate for gestational age

Abstract: Objective: Sleep disturbances and alterations of diurnal endocrine rhythms are associated with increased risk of type 2 diabetes (T2D). We previously showed that young men born small for gestational age (SGA) and with increased risk of T2D have elevated fat and decreased glucose oxidation rates during nighttime. In this study, we investigated whether SGA men have an altered diurnal profile of hormones, substrates and inflammatory markers implicated in T2D pathophysiology compared with matched individuals born … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In addition, a report on human and rodent animal demonstrated that ICP was also associated with sex-specific increased susceptibility to severe obese, diabetic phenotype with hepatosteatosis in adult offspring, indicating a programming effect of the high bile acid exposure in utero 12,13. Small for gestational age (SGA), defined as fetal weight less than the 10th percentile based on gender and gestational age, is one of the leading causes for stillbirth, neonatal death and perinatal morbidity [14][15][16] . Several epidemiological reports showed that the risks of autism in childhood and cardiovascular and metabolic diseases in adulthood were increased in people born with SGA [17][18][19][20] . Nevertheless, no report analyzed the association between ICP and an increased risk of SGA infants in a cohort study.…”
mentioning
confidence: 99%
“…In addition, a report on human and rodent animal demonstrated that ICP was also associated with sex-specific increased susceptibility to severe obese, diabetic phenotype with hepatosteatosis in adult offspring, indicating a programming effect of the high bile acid exposure in utero 12,13. Small for gestational age (SGA), defined as fetal weight less than the 10th percentile based on gender and gestational age, is one of the leading causes for stillbirth, neonatal death and perinatal morbidity [14][15][16] . Several epidemiological reports showed that the risks of autism in childhood and cardiovascular and metabolic diseases in adulthood were increased in people born with SGA [17][18][19][20] . Nevertheless, no report analyzed the association between ICP and an increased risk of SGA infants in a cohort study.…”
mentioning
confidence: 99%
“…In addition, no studies on PYY secretion levels in individuals born SGA have been reported. One study found no significant difference in GLP-1 secretion levels between adults born SGA and AGA ( 10 ). We found that in children aged 4-8 years, GLP-1 and PYY levels were lower in the SGA group than in the AGA control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies ( 9 , 10 , 11 ) have focused on gastrointestinal hormone levels in children born SGA. The data are unclear about whether catch-up growth leads to inappropriate secretion of gastrointestinal peptides and whether they are involved in the long-term metabolic outcomes in children born SGA.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained from both animal [ 97 , 98 ] and clinical [ 99 , 100 ] studies. Other adipokines, such as visfatin [ 101 , 102 , 103 ], vaspin [ 104 ], retinol binding protein 4 (RBP4) [ 105 ], apelin [ 106 ], and resistin [ 107 ] were shown to have a rhythmic secretion profile. Additionally, shift work was found to result in elevated serum resistin [ 108 , 109 ].…”
Section: The Role Of Circadian Rhythm In Adipose Tissue Functionmentioning
confidence: 99%